Effect of Yttria Content up to 15wt% on Mechanical Properties of Al-Y2O3 Composites Prepared Via Squeeze Casting and Powder Metallurgy Routes - Mahdi, Farouk M.; Annaz, Abd-Ulkader A. (Sulaimani Journal for Engineering Sciences, 2015)
In this study Al - (0-15 wt %) Y2O3 composites were prepared by both squeeze casting and powder metallurgy routes. It was found throughout this work that Vickers microhardness, compressive yield strength and wear resistance increase continuously with increasing Yttria content up to 15wt% despite the preparing method. Powder metallurgy composites showed higher hardness and compressive strength compared with those of squeeze casting. On the other hand, both squeeze casting, at squeeze pressure of 15 and 20 MPa, and powder metallurgy routes gave approximate wear rates except that of pure aluminum where squeeze casting specimens showed much lower wear rates than those of powder metallurgy. It was also found that squeeze pressure has great effect on grain refining and Chinese script microstructure evolution. XRD patterns reveal high level of harmful oxides and intermetallic compounds in squeeze casting composites as compared with those prepared by powder metallurgy technique.
Keywords: Al-Y2O3 composites; mechanical properties; squeeze casting; powder metallurgy